Use of savolitinib as neoadjuvant therapy for non–small cell lung cancer patient with MET exon 14 skipping alterations: A case report - Zhang, Yu; Zhang, Hao; Wang, Hanqing; Zeng, Jingtong; Zhang, Bo; Zhou, Ning; Zu, Lingling; Song, Zuoqing; Wang, Changli; Xu, Song (Frontiers in Oncology, 2022)
Savolitinib is a tyrosine kinase inhibitor being developed for the treatment of metastatic non-small cell lung cancer (NSCLC) with mesenchymal-epithelial transition factor (MET) exon 14-skipping alterations. However, the role of savolitinib in neoadjuvant therapy for lung cancer remains unclear. Herein, we present a case of a 65-year-old woman diagnosed with stage IIIA (cT2bN2M0, 8th TNM stage) upper right lung adenocarcinoma harboring MET exon 14-skipping alterations. After four weeks of therapy, a partial response was achieved with neoadjuvant savolitinib, and significant shrinkage in tumor and lymph nodes was observed. We also measured the immune microenvironment of the primary tumor pre- and post-treatment with savolitinib.